2020
DOI: 10.1007/s11427-019-1753-3
|View full text |Cite
|
Sign up to set email alerts
|

Sodium cantharidinate, a novel anti-pancreatic cancer agent that activates functional p53

Abstract: Despite the use of many types of chemotherapies for pancreatic cancer, optimal efficacy has not been obtained so far. Pancreatic cancer shows a high incidence of TP53 mutations, inactivating its tumor suppressor activity. In this study, we identified sodium cantharidinate as a novel, potential anti-pancreatic cancer agent that activates p53 function. Sodium cantharidinate reduced the viability of pancreatic cancer cells, including the human primary pancreatic cancer cells, PANC-1, AsPC-1, SW1990 and BXPC-3, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The analysis results of the PPI indicated that CASP3 has the most degree scores, which means CASP3 could be the essential protein for 1 ( Figure 5 A,B). We verified it via a Western blot experiment in vitro and found that 1 could affect CASP3 expression ( Figure 5 C), which reportedly plays a crucial role in the cell apoptosis pathway [ 33 , 34 , 35 ]. Therefore, we hypothesized that 1 might promote BXPC-3 apoptosis by affecting the activation of CASP3.…”
Section: Resultsmentioning
confidence: 77%
“…The analysis results of the PPI indicated that CASP3 has the most degree scores, which means CASP3 could be the essential protein for 1 ( Figure 5 A,B). We verified it via a Western blot experiment in vitro and found that 1 could affect CASP3 expression ( Figure 5 C), which reportedly plays a crucial role in the cell apoptosis pathway [ 33 , 34 , 35 ]. Therefore, we hypothesized that 1 might promote BXPC-3 apoptosis by affecting the activation of CASP3.…”
Section: Resultsmentioning
confidence: 77%
“…Among all the derivatizations, salt formation has been one of the most interesting due its simplicity. For example, sodium cantharidinate (Figure 9, 9h) induced apoptosis and DNA fragmentation of pancreatic cancer cells (PANC-1) with perturbation in p53 signaling pathway [124]. Kian's group tested this salt against breast cancer and detected apoptosis and cell cycle arrest with possible implication of p53 [125].…”
Section: Oxanorbornene Derivativesmentioning
confidence: 99%
“…Furthermore, SCA can induce HepG2 cell apoptosis via the LC3 autophagy pathway ( Tao et al, 2017 ). Moreover, in pancreatic cancer cells, SCA exerts antitumor effects by activating p53 ( Liu et al, 2021 ). However, the application of SCA for breast cancer treatment has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%